4-(4-Hydroxybenzoyl)phenol monohydrate - Li, He-Ping; Yang, Yun-Xia; Ng, S.W. (International Union of Crystallography, 2010)
The aromatic rings of the title compound, C13H10O3 center dot H2O, are aligned at dihedral angles of 20.6 (1) and 40.8 (1)degrees with respect to the triangular C-aryl-C(=O)-C-aryl fragment. The hydroxy groups are each hydrogen-bond donors to separate water molecules, the water molecule itself being hydrogen-bonded to one hydroxy group and one carbonyl group. The water molecule exists in an unusual four-coordinate environment in the resulting layer structure.